A CONTRASTIVE ANALYSIS OF ADJECTIVE CLAUSE ON SPIDERMAN HOME COMING - Munthe, Eka Ria Oktavia Ginting; Marbun, Nova; Torong, Silvia; Sitanggang, Anita (Transpublika Publisher, 2022)
This research focuses on the contrastive analysis of adjective clauses found in the Spiderman Homecoming movie. The research design used is a qualitative design. The researcher conducted this research descriptively, which explained the research by making a table and a few sentences to explain it. The data is taken from the Spiderman Homecoming movie. Researchers search and find data from various websites to obtain data by reading and searching for materials in journals, e-books, and related articles. The researcher discusses everything related to the adjective clause, which is the main purpose of this research. The sentences or scripts are taken and analyzed through an adjective clause. The results of the researcher's analysis found 2 types of adjective clauses, namely, adjective clause defining and adjective clause modifying. In the Spiderman: Homecoming film script, there are 25 adjective clause defining sentences and 14 adjective modifying sentences.